Bridging the intracranial pressure gap: a smooth transition strategy for slit ventricle syndrome. Issue 7 (15th July 2021) - Yoon, Sang-Youl; Kim, Seung-Ki; Phi, Ji Hoon
Abstract: Slit ventricle syndrome (SVS) is a well-known complication of long-standing shunts. Patients develop intermittent severe headache, vomiting with other symptoms of increased intra-cranial pressure. Brain computed tomography (CT) usually reveals slit-like ventricles with nearly obstructed proximal catheters. Treatment for SVS usually involves upgrading the shunt valve pressure setting. Currently, many patients carry programmable shunts and pressure setting can be adjusted noninvasively. However, when the programmable valve pressure setting is upgraded, some patients with SVS experience worsened symptoms. This is caused by the time gap between ICP increase and real ventricular expansion (and freeing proximal catheter) after shunt upgrading. Therefore, it is important to control a patient's symptoms during the transition period. We report our experience in controlling ICP in a patient with SVS using external ventricular drainage.